Electric Power in the Paraíba Valley, Brasil: Companies; Entrepeneurs and the State in the Construction of the Electric Power Sector (1900-1970) - Ricci, Fabio (2015)
This article examines the transformation process undergone by the electrical system in the Paraíba Valley in the state of São Paulo and discusses the possibilities for developing the cities located along the transmission lines between the metropolises of Rio de Janeiro and São Paulo. From the 1930s to the 1950s, the Paraíba Valley went from a region whose electrical sector was fragmented and run by municipal enterprises, to one with an electrical system connected to the system of the Light company, and, finally, from the 1960s, the region began to receive its electricity from state companies. This study traces the trajectory of the electricity sector in this region and examines the relationship between this sector and economic development.